Effect of different mucoadhesive polymers on release of ondansetron HCl from intranasal mucoadhesive in situ gel - Nidhal K. Maraie; Yasser Qasim Almajidi (College of Pharmacy / Mustansiriyah University, 2018)
The aim of this work was to promote an intranasal mucoadhesive drug allocation system to simplify the systemic delivery of ondansetron HCL (OND-HCl) for the immediate and sustain prevention of repeated nausea and vomiting caused by the initial and repeated courses of anticancer therapy. An in situ gel dosage form was used to raise the permanence time and hence the absorption of OND-HCl from nasal mucosa. Temperature stimulated in situ gel formulations were intended by cold method using polymers like kolliphor 407, chitosan and HPMC E15. A mixture of polysorbate 20 and ethanol (1: 2 ratio) was used as solvent to dissolve the drug. The pH of in situ gel solution was measured to pH range (4.5-6.5). The six in situ gel formulas were characterized for gelation temperature, pH, viscosity, drug content, mucoadhesion and dissolution release .The temperatures of conversion of all the formulas solution to gel were within the range of 30-43ºC. The drug content of all six in situ gel formulas showed drug content uniformity (99.15-99.76%). Dissolution release of the drug from in situ gel formulas showed immediate and sustained release features with Higuchi model and zero order model mechanisms